2008
DOI: 10.1074/jbc.m800732200
|View full text |Cite
|
Sign up to set email alerts
|

Prothyrotropin-releasing Hormone Targets Its Processing Products to Different Vesicles of the Secretory Pathway

Abstract: Prothyrotropin-releasing hormone (pro-TRH) is initiallycleaved by the prohormone convertase-1/3 (PC1/3) in the transGolgi network generating N-and C-terminal intermediate forms that are then packed into secretory vesicles. However, it is not known whether these peptides are differentially sorted within the secretory pathway. This is of key importance because the processing products of several prohormones fulfill different biological functions. Using AtT20 cells stably transfected with prepro-TRH cDNA, we found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 50 publications
0
23
1
Order By: Relevance
“…In contrast, although there was a tendency, no significant differences were observed in PC1 gene expression between the groups (Fig. 1C), even though Perello et al (20) have reported that PC1 is a specific convertase involved in proTRH processing as a regulator step in TRH activity in many tissues.…”
Section: Resultscontrasting
confidence: 43%
“…In contrast, although there was a tendency, no significant differences were observed in PC1 gene expression between the groups (Fig. 1C), even though Perello et al (20) have reported that PC1 is a specific convertase involved in proTRH processing as a regulator step in TRH activity in many tissues.…”
Section: Resultscontrasting
confidence: 43%
“…An increase in the sorting efficiency of proglucagon after cleavage at K70R71 in the Golgi would be similar to the observations with prothyrotropin-releasing hormone (pro-TRH), where processing by PC1/3 enhances the sorting of pro-TRH-derived peptides into granules (Mulcahy et al 2005). Future experiments will investigate more closely the role of processing in proglucagon sorting, and the possibility that the products of this initial processing, glicentin and the major proglucagon fragment (MPGF) are sorted into different granule populations, again in a pattern similar to that of pro-TRH sorting (Perello et al 2008).…”
Section: Discussionmentioning
confidence: 81%
“…That the sequences of glucagon and GLP-1 are highly conserved (32) lends evidence to this reasoning. This is in contrast to pro-thyrotropin-releasing hormone, where PC1/3-mediated processing early in the secretory pathway is required for efficient sorting to distinct subpopulations of granules (61,62).…”
Section: Discussionmentioning
confidence: 99%